Non-Functioning Pancreatic Neuroendocrine Tumor Accompanied with Multiple Liver Metastases: Remorseful Case and Literature Review - Hori, Tomohide; Takaori, Kyoichi; Kawaguchi, Michiya; Ogawa, Kohei; Masui, Toshihiko; Ishii, Takamichi; Nagata, Hiromitsu; Narita, Masato; Kodama, Yuzo; Uza, Norimitsu; et al. (JOP. Journal of the Pancreas, 2014)
Context Pancreatic neuroendocrine tumor (P-NET) is a rare and slow-growing tumor. Unfortunately, there is no clear consensus on the role and timing of surgery for primary tumor and liver metastases, although current reports refer to liver surgery including LT for unresectable liver metastases. Case report A thirty-nine-year-old man was diagnosed with nonfunctioning pancreatic neuroendocrine tumor (P-NET) in the pancreatic head, with multiple liver metastases. The tumor was 2.5 cm in diameter and he was asymptomatic. Small but multiple metastases were detected in the liver, and no extrahepatic metastases were observed. We initially intended to control the liver metastases before resection of the primary tumor. To begin with, transarterial chemoembolization (TACE) and transcatheter arterial infusion (TAI) were repeated. Thereafter, systemic chemotherapy and biotherapy were introduced according to follow-up assessments. Unfortunately, imaging assessment at about 10 months later revealed that liver metastases were partially enlarged, although some were successfully treated. Therefore, these therapies were switched to other regimens, and TACE/TAI, systemic chemotherapies and biotherapies were repeated. Although liver metastases seemed to be stable for a while, the primary tumor was enlarged even after therapy. At 3.5 years after initial diagnosis, the primary tumor became symptomatic (pain and jaundice). Liver metastases enlarged and massive swelling of the para-aortic lymph nodes was observed. Thereafter, palliative therapy was the main course of action. He died at 4.3 years after initial diagnosis. Conclusion Our young patient could have been a candidate for initial surgery for primary tumor and might have had a chance of subsequent liver transplantation for unresectable metastases. Surgeons still face questions in deciding the best surgical scenario in patients with P-NET with liver metastases. Image: Primary tumor grew after therapy.